Be mine - Ford, Richard, 1944- (Ford, Richard, 1944- Frank Bascombe book., 2023)
"From Pulitzer Prize winner Richard Ford: the final novel in the world of Frank Bascombe, one of the most indelible characters in American literature Over the course of four celebrated works of fiction and almost forty years, Richard Ford has crafted an ambitious, incisive, and singular view of American life as lived. Unconstrained, astute, provocative, often laugh-out-loud funny, Frank Bascombe is once more our guide to the great American midway. Now in the twilight of life, a man who has occupied many colorful lives-sportswriter, father, husband, ex-husband, friend, real estate agent--Bascombe finds himself in the most sorrowing role of all: caregiver to his son, Paul, diagnosed with ALS. On a shared winter odyssey to Mount Rushmore, Frank, in typical Bascombe fashion, faces down the mortality that is assured each of us, and in doing so confronts what happiness might signify at the end of days. In this memorable novel, Richard Ford puts on displays the prose, wit, and intelligence that make him one of our most acclaimed living writers. Be Mine is a profound, funny, poignant love letter to our beleaguered world"--